2019
DOI: 10.1029/2018wr024652
|View full text |Cite
|
Sign up to set email alerts
|

Wetland Connectivity Thresholds and Flow Dynamics From Stage Measurements

Abstract: Depressional wetlands are dominant features in many low‐gradient landscapes, where they provide water storage and exchange. Typical basin morphology enables water storage during drier periods, when surface flow paths are disconnected and exchange is limited to slower groundwater flow paths. Under wetter conditions, wetland stage can exceed surface connection thresholds, activating surface flow paths to downstream waters. Empirical methods are needed to quantify these dynamics and thus to assess their role in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 57 publications
(109 reference statements)
5
31
0
Order By: Relevance
“…It also indicates that the topography in BICY is statistically stationary (Figure 4), resulting in conditions where a limited sampling of basin‐scale topography using a single DEM of 500 m radius, which contains multiple wetlands (pattern period ≈ 200 m), is sufficient to characterize whole‐landscape variability and patterns in elevation. Moreover, stage dynamics were highly correlated among wetlands (Figure 3) despite often large distances between them, which is consistent with our model conceptualization of distributed wetland storage acting as a single reservoir, and with recent work highlighting synchronous wetland stage and imputed spill dynamics among multiple BICY wetlands (McLaughlin et al, 2019). This, in turn, enables the fitting of a consistent “rating curve” for the stage‐discharge relationship across all wetlands (Figure 2 and Equation ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It also indicates that the topography in BICY is statistically stationary (Figure 4), resulting in conditions where a limited sampling of basin‐scale topography using a single DEM of 500 m radius, which contains multiple wetlands (pattern period ≈ 200 m), is sufficient to characterize whole‐landscape variability and patterns in elevation. Moreover, stage dynamics were highly correlated among wetlands (Figure 3) despite often large distances between them, which is consistent with our model conceptualization of distributed wetland storage acting as a single reservoir, and with recent work highlighting synchronous wetland stage and imputed spill dynamics among multiple BICY wetlands (McLaughlin et al, 2019). This, in turn, enables the fitting of a consistent “rating curve” for the stage‐discharge relationship across all wetlands (Figure 2 and Equation ).…”
Section: Resultssupporting
confidence: 91%
“…The hydroperiod varies with elevation across the landscape, with many domes being perennially inundated, while the surrounding uplands, at approximately 50 cm higher elevation, are dry most of the year (Cohen et al, 2011). Flow patterns and surface connectivity depend on stage, with connected surface flow among domes at high stage in contrast to limited wetland‐groundwater exchange at low stage (McLaughlin et al, 2019). Construction of roads for logging, oil drilling, and recreation over the last century has resulted in augmented landscape drainage through canals.…”
Section: Study Site and Experimental Descriptionmentioning
confidence: 99%
“…While it is broadly tenable that the observed pattern is contemporary and that local divergence in elevation is induced by markedly differing weathering environments between wetlands and uplands (i.e., the positive dissolution feedbacks are clear), the negative feedbacks that inhibit dissolution features, preventing continual expansion either vertically (collapse sinkholes) or laterally are less clear. One key recent insight is that vertical expansion is limited by the absence of subsurface drainage (McLaughlin et al, ) as well as persistent shallow water table conditions. Moreover, vertical weathering rates are self‐limiting as insoluble residual materials accumulate as wetland sediment (Watts et al, ), effectively sealing carbonic acid production in the shallow sediments from unweathered bedrock at depth (Dong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research provides some evidence that catchment‐scale RWU strategies could be derived from surface water observations. McLaughlin et al () observed evapotranspiration signals within wetland stage measurements. Similarly, Tashie et al () demonstrated that streamflow recessions in a headwater catchment in the southern Appalachian Mountains reflected both gravity‐driven groundwater outflow to surface waters as well as forest transpiration.…”
Section: Introductionmentioning
confidence: 99%